Leader – A Hero or A Tyrant? - Dzwonkowska, Dominika (Roczniki Filozoficzne, 2025)
The article is a polemic with Jarosław Kucharski’s text “The Main Problems of Leadership Ethics,” in which I present a reflection on the moral dimension of a leader’s actions, who in the sphere of praxis faces the dilemma of reconciling efficiency and effectiveness with moral values. In my commentary, I focus on two aspects related to the discussion of leadership presented by Kucharski. Firstly, I analyze the problems related to the linguistic layer of the term “leader” and various terms related to leadership, such as the terms “follower (of the leader)” or “servant leadership.” The second significant issue is the heroic image of the leader in the literature on which Kucharski bases his research. The leader appears as a heroic figure who leads the organization in an exemplary manner and is ready for heroic deeds. Such a delineated image of leadership seems not to fit the business realities.